PENGEMBANGAN KREATIVITAS GENERASI Z - Mei Ie; Atalya Fransiska (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Creativity is one of the abilities that every individual needs to have because of its nature that is important for selfdevelopment. To be able to survive the changes that occur, creativity is needed to continue to develop and produce new things. Creativity is the ability to create new discoveries or an ability to develop existing discoveries better than before. Creativity can grow through two main environments, namely the family environment and the school environment. Therefore, this activity is carried out in the scope of the school which is one of the main environments of creativity growth. Basically, every individual is creative. Currently the generation that is in concern is the younger generation or generation Z. Generation Z is also often referred to as the post-millinealgenerai,which in the development of personality and skills, are in the uncertainty and complexity of the socioeconomic environment. In addition, generation Z also strongly considers that his life depends on the advancement of existing technology, even until the future of his organized life. Generation Z is a future generation that will face more and more opportunities and challenges in conditions of uncertainty. To deal with the uncertainty and risks of the future, it is imperative for Generation Z to develop their creativity and increase their competitive advantage. The method of carrying out activities is to conduct deepinterviews, study relevant literature, draw up seminar and workshopactivity plans, implementation of PKM activities, evaluation of activities, and preparation and submission of activity reports. In general, community service activities have been going well and the students also give a positive response and hope this activity can be carried out continuously.